Does the digital economy drive low-carbon urban development? The role of transition to sustainability - Yu, Wentao; Lan, Ning; Tan, Xiaolan; Zhang, Shanshan; Chen, Jinyan (Frontiers in Ecology and Evolution, 2023)
The rapid expansion and implementation of digital technologies are profoundly changing our lifestyles, production methods, and modes of exchange. However, whether or not such change can help promote the sustainability of urban socio-environmental systems has not been fully investigated.In this paper, we propose a comprehensive framework that utilizes the spatial Durbin model to investigate whether and how the digital economy contributes to low-carbon urban development, using the panel data of 276 Chinese cities from 2011 to 2018. This framework systematically identifies triple dimensions of low-carbon transition taking place throughout the whole value chain system, i.e. green innovation, production reshaping, and consumption upgrading. The finding reveals that the digital economy in a city exerts a significant mitigating effect on carbon emissions in both local and neighboring cities. It is also observed that digital economy activities play a significant role in alleviating urban carbon emissions due to their capacity to stimulate green innovation and promote sustainable patterns of production and consumption. The robustness of these findings is assessed through the consideration of endogeneity and substitution of the explained and explanatory variables. This paper contributes to a systematic understanding of the linkage between the revolution of digitalization within economic systems and the transition towards sustainability within environmental of 删除[余文涛]: